Arti Penting Kepatuhan Pembayaran Dan Pelaporan Spt Tahunan Orang Pribadi Terhadap Pemahaman Peraturan Perpajakan - Lenny Lenny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Taxpayers are individuals or entities that have tax rights and obligations in accordance with applicable regulations. If the taxpayer has a minimal understanding of tax regulations, it will result in non-compliance with the applicable tax rules, so that the end result will also result in a minimal level of mandatory compliance and an impact on the low level of tax that will be received by the state, as well as if the level of compliance of the taxpayer is low. In a country, a decrease in tax revenue will also result, and one of the indicators is that taxpayers must be disciplined in reporting SPT on time. Descriptive associative research is a type of research that uses direct data derived from 60 questionnaires completed by 60 respondents who are individual taxpayers and will be used entirely. This study uses a quantitative analysis method, which is carried out by conducting statistical tests on the results of the questionnaire obtained with the SP application SS in processing the questionnaire data obtained from respondents. Compliance with the payment and reporting of individual annual tax returns has a positive and significant impact on the understanding of tax regulations. Keyword : Tax payer compliance, Tax, Tax regulations understanding